Analysis of Audience Reception to TikTok Content @Vmuliana as an Educational Media in the Career Field - Sinaga, Naomi Septiana; Sahputra, Dedi; Khairullah, Khairullah (UMSU, 2024)
This research aims to find out how the audience accepts the analysis of the TikTok account @vmuliana regarding career education content. Then it is divided into three meaning positions, namely Dominance, Negotiation and Opposition using the Reception approach theory according to Stuart Hall. The informants in this research were followers and non-followers of the TikTok account @vmuliana to get the audience's meaning after watching the educational content. This research uses qualitative research methods, collecting data through in-depth interviews with six informants who are active audiences who have watched educational content from Vina Muliana. The results of this research show that TikTok social media users give different meanings to the messages conveyed by the media according to the informant's point of view. Dominant Hegemony Position Category, namely the informant agrees that Vina Muliana's educational content provides a lot of information and is very useful in the career field. Negotiation Position Category, namely informants who benefit from the content but also have different views. Opposition category, namely informants who think the content is too focused on general methods that many people already know.